Cost-effectiveness analysis of lopinavir, ritonavir, and nevirapine toward HIV AIDS patients as antiretroviral: a systematic review - Pratama, Anggara Martha; Pramestutie, Hananditia Rachma; Krisnadewi, Kadek Ida; Pratiwi, Hening (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2023)
Background: The mobilization of resources to prevent and treat human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) is unparalleled in the history of public health. Nevirapine resistance may decrease the effectiveness of viral suppression with nevirapine-based HIV in women infected with human immunodeficiency virus (HIV) with previous exposure to single-dose nevirapine. However, the alternative lopinavir/ritonavir–based antiretroviral therapy (ART) regimen is more expensive. Objective: Our objectives were to project the tradeoffs regarding the cost-effectiveness of ART regimens for nevirapine-exposed and lopinavir/ritonavir. Methods: A thorough literature search was conducted using PubMed and SAGE databases, employing search terms such as “cost-effectiveness analysis,” AND “HIV AIDS,” AND “lopinavir,” OR “ritonavir,” AND “nevirapine.” Additionally, hand searches were carried out on Google Scholar with various combinations of these terms to ensure comprehensive coverage of relevant studies. Results: Six studies met the our inclusion criteria and were reviewed. The analysis confirms that both nevirapine and lopinavir/ritonavir-based ART regimens are cost effective in a range of settings, despite differences in their relative efficacy and contexts in which they are used. Conclusion: This systematic review collates recent studies on the cost-effectiveness of nevirapine and lopinavir/ritonavir in ART. It showed that in this finding, there are cost effective but this article had wide variation with comparison therapy. Cost-effectiveness results depended on the relative efficacy of lopinavir/ritonavir and nevirapine in both first-line and second-line ART.